FROM PROPHETIC THEOLOGY TO PROPHETIC SOCIAL SCIENCE: The Study of Kuntowijoyo’s Thought - Arifka, Angga (Jurnal Studi Islam dan Sosial, 2025)
This article attempts to explore contemporary readings of theology. In classical and medieval times, Islamic theology is regarded as a scientific discourse that discusses such metaphysical issues as God, the status of the Quran, eschatology, and other things that include beliefs or principles of faith in Islam with rational arguments. This article as library research uses a qualitative-descriptive approach by exploring primary and secondary sources in the form of textual sources. Employing content analysis approach, this article found that there has been a shift in views on theology in contemporary times. In addition, this article concludes that prophetic social science can become an epistemological and methodological foundation in building transformative and contextual social science. The novelty of this article lies in the fact that prophetic social science is not a normative discourse, but as an integrative epistemological model that eliminates the dichotomy between revelation and reason, between values and facts, and between science and social practice.